LIA-QMS method for the quantity analysis of the hydrogen isotopes retention in first-wall components of Globus-M2 tokamak - O.S. Medvedev; A.G. Razdobarin; E.V. Shubina (Smirnova); M.V. Grishaev; D.I. Elets; L.A. Snigirev; A.S. Kolomiytsev; A.V. Nikolaev (Nuclear Materials and Energy)
The technique based on quadrupole mass spectrometry of the material ejected by laser-induced ablation – LIA-QMS is proposed as a tool to measure H/D/T content in carbon co-deposits in the first wall and divertor regions of tokamak reactors. Tungsten tiles exposed in Globus-M2 tokamak were taken for validation experiments. Measurement accuracy was determined by comparison with the results obtained by laser-induced desorption – LID-QMS and conventional thermal desorption spectroscopy (TDS). Total amount of deuterium in hydrocarbon deposits was found to be 2.8 × 1017 D/cm2, when measured by – LIA-QMS, 3.0 × 1017 D/cm2 for LID-QMS and 2.9 × 1017 D/cm2 for TDS. The main uncertainty of D surface concentration are caused by inhomogeneity of the deposit thickness over the sample area or by presence of hydrocarbon species in the released gas.